Effects of genetic variants of ADH1B and ALDH2 and social network on continued alcohol drinking among young adolescents in Taiwan. (1st February 2015) - Ting, Te-Tien; Huang, Shiao-Yun; Chen, Kuang-Hung; Tseng, Ching-Ing; Lin, Keh-Ming; Chen, Chuan-Yu; Chen, Wei J.
Abstract: Background: This study aimed (i) to evaluate the effects of genetic variants of ADH1B and ALDH2 and social network position on continued alcohol use in early adolescence, and (ii) to explore possible moderating role of pubertal development on genetic effects. Methods: The sample comprised 496 children who ever drank alcohol before the ages of 10–12. Information pertaining to sociodemographic background, pubertal development, parental drinking, alcohol and tobacco use, alcohol-metabolizing genes, and nominated best friends was collected in four waves of assessment. Polymorphisms of ADH1B (rs1229984) and ALDH2 (rs671) were genotyped. The latent class analysis was first used to characterize longitudinal alcohol use pattern, followed by the multinomial logistic regression analyses to assess its association with genes, pubertal development, and social network. Results: Three distinct classes of alcohol users (i.e. ex-drinkers, sporadic drinkers, and continued drinkers) were derived from alcohol-experienced children. Both alcohol-metabolizing genes appear to have protective effects, yet such relationships were only significant for youngsters in pre-to-early pubertal stage: the adjusted odds ratio (aOR) of ADH1B fast-genotype for sporadic drinkers was 0.46 and that of ALDH2 slow-genotype for both sporadic and continued drinkers was 0.47 and 0.42, respectively. Children having the bridge position in their peer network were more likely to be sporadic drinkers (aOR = 4.15) and continued drinkers (aOR = 3.16). Conclusions: Our results illustrate a potential moderating effect of pubertal development on the protective influence of alcohol-metabolizing genes on subsequent alcohol use among alcohol-experienced children as well as the independent contribution of early life's social network to their alcohol involvement.